2014
DOI: 10.1371/journal.pone.0097622
|View full text |Cite
|
Sign up to set email alerts
|

Olive Phenolics as c-Met Inhibitors: (-)-Oleocanthal Attenuates Cell Proliferation, Invasiveness, and Tumor Growth in Breast Cancer Models

Abstract: Dysregulation of the Hepatocyte growth factor (HGF)/c-Met signaling axis upregulates diverse tumor cell functions, including cell proliferation, survival, scattering and motility, epithelial-to-mesenchymal transition (EMT), angiogenesis, invasion, and metastasis. (-)-Oleocanthal is a naturally occurring secoiridoid from extra-virgin olive oil, which showed antiproliferative and antimigratory activity against different cancer cell lines. The aim of this study was to characterize the intracellular mechanisms inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
257
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(274 citation statements)
references
References 45 publications
10
257
0
Order By: Relevance
“…Interestingly, mutated BRAF is associated with an aggressive disease phenotype (8) and our findings demonstrated that oleocanthal was able to induce cytotoxicity in both cell lines with similar IC 50 values. Our results are in line with those showing that oleocanthal inhibits the growth of human breast cancer cell lines MDA-MB-231, MCF-7, and BT-474, without affecting normal human MCF10A cell growth (9). Noteworthily, selective antitumor effect by oleocanthal has been reported to be associated, at least partially, to its ability to induce lysosomal membrane permeabilization leading to apoptosis and/or necrosis.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, mutated BRAF is associated with an aggressive disease phenotype (8) and our findings demonstrated that oleocanthal was able to induce cytotoxicity in both cell lines with similar IC 50 values. Our results are in line with those showing that oleocanthal inhibits the growth of human breast cancer cell lines MDA-MB-231, MCF-7, and BT-474, without affecting normal human MCF10A cell growth (9). Noteworthily, selective antitumor effect by oleocanthal has been reported to be associated, at least partially, to its ability to induce lysosomal membrane permeabilization leading to apoptosis and/or necrosis.…”
Section: Discussionsupporting
confidence: 91%
“…38 This study presented data implicating suppression of c-Met as a critical consequence of OC treatment although it was not clear whether LMP was involved in cell death or PARP cleavage was observed. Nonetheless, the study demonstrated that OC has similar effects in an animal model to those described in the current study with minimal effects on normal cells, thus reinforcing the potential of OC as a therapeutic agent in breast and other cancers.…”
Section: Discussionmentioning
confidence: 88%
“…More recent studies, for instance those by Akl and colleagues, confirmed the anticancer effects of OC treatment in breast cancer. These authors observed that OC was able to reduce c-Met kinase activity, cell growth, migration, and invasion of breast cancer cells and tumorigenicity in a mouse model [27] (Fig. 3).…”
Section: Chemopreventive and Chemotherapeutic Effects Of Ocmentioning
confidence: 88%